Die reg op inligting: 'n regsteoretiese begronding - Plessis, W. du (Koers, 1987)
In this article the author discusses the theoretical background to a right to information. Recent events as the restriction on information regarding the 1975-1976 Angolan war, the Information Scandal in 1977-1978, and the regulations regarding the distribution of information during the present state of emergency are only some examples of the way in which the state withholds information from the individual. Very few countries in the world can claim domestic peace. Economical, political and social affairs have to be adapted constantly. In this process the administration of the state grows, and with it, bureaucracy. Private concerns group together and form powerful organizations. The individual plays an increasingly insignificant role in this society and his rights and liberties are encroached upon in a variety of ways.